Focus on the Translation Trainee - Pietrzak, Paulina; Kornacki, Michał (Research in Language, 2021)
A learner-based approach to translator training has already been recognised and discussed in translator education for the last few years (González-Davies 2004; Kelly 2005; Kiraly 1995, 2000; Massey et al. 2019). With the main focus on learning rather than training and the translator rather than the product or the process of translation, the observed trend in translation studies can be called ‘translator studies’ (Chesterman 2009). The tendency has been for the teacher-centred approach to be gradually replaced by manners of teaching which favour learner autonomy (Gonzalez Davies 2004). Nonetheless, due to the multiple demands that translator teachers must fulfil, they still happen to be regarded as the main active performers in the educational process. Invaluable as the teacher’s agency is for shaping the educational reality that translation trainees experience, translator education requires ensuring that student-oriented education actually involves freeing teachers and students from their traditional roles, to break out of the routine in which they have been rooted for years. It is worth emphasising that the roles and responsibilities of the translator teacher and student are equally important. The article looks at the translation educational process with the main focus on trainees who are supposed to build their career in the uncertain and indeterminate translation industry of the future.